Portuguese as a Foreign Language (PFL) teacher’s education in a language center in a university context - Consolo, Douglas Altamiro (2021)
In this paper, I report on experiences of Portuguese as a foreign language (PFL) teacher education, as pre-service teacher development, in a language center and teacher development extension project at IBILCE-UNESP. Portuguese teacher development in the Letters degree at that university has currently been restricted to only one compulsory course subject about PFL in the curriculum, and to students’ participation in extension projects. On the other hand, Letters undergraduates who act as teachers in the CLDP-IBILCE have the opportunity to reflect about the teaching and learning of PFL, to plan courses and course materials, and to teach PFL lessons in co-teaching partnerships with their supervisor. The complementary experience of teacher development in the CLDP has proved to be very satisfactory, besides the fact that PFL courses can be offered to students from both the university and the outside communities.